Jail Information System of the Provincial Jail of Misamis Oriental - Tubongbanua, Jun Brian P.; De Ocampo, Mae Ann F.; Pabualan, Rhoderick Z.; Salvador, Jose Rafael P.; Turno, Kurt Andersen M.; Perocho, Laurence M. (JPAIR Multidisciplinary Research, 2010)
Keeping track of inmates' profile in the Provincial Jail is a constant challenge, especially as they move from one part of facility to another or from Misamis Oriental Provincial Jail to any Prison within the country and also the growing population of the inmates is a big problem in keeping track of inmate's profile. In an effort to improve the tracking of inmates, we conducted a study on how the authorities of the provincial jail are keeping the records of the inmates. We found out that the major problems are; redundancy of inmate's profile, unorganized tracking of inmate's profile, and time - consuming in the generation of jail reports. Our Objective in making this program is to make the job of the provincial jail employees easier. The employees of the Provincial Jail need to keep in track of the profile of the inmates. So we decided to make a computer - based Jail Information System which aims to solve the redundancy of prisoner's profile, organize the tracking of prisoner's records, and to generate reports on time. The system allows accurate generation of jail reports. Jail reports are generated faster compared to the manual system which takes a lot of time to complete the entire search for an inmate's personal information. Being efficient, the proposed system is an advantage to both the institution and its personnel.
Keywords: provincial jail; information system; Misamis Oriental